Orthodontic-prosthetic rehabilitation of alveolar cleft - Yash Salkar; Shubhaani Singh; Anu Singla; Suruchi Sindwani (Wolters Kluwer Medknow Publications, 2023)
This case report presents the treatment of an 18-year-old girl with a unilateral alveolar cleft and impacted deciduous teeth. The patient had a gap in her upper front teeth and sought treatment for the alveolar defect. The initial treatment plan included alveolar bone grafting, fixed mechanotherapy, and prosthetic rehabilitation. However, the patient declined the bone grafting surgery. To address the issue, orthodontic treatment began with the extraction of a lower incisor to correct the overjet and the removal of over-retained deciduous teeth and a resorbed lateral incisor. The impacted lateral incisor was brought into the arch to stimulate bone formation. The treatment lasted 21 months, and an interim prosthetic rehabilitation with a natural tooth pontic was placed before the final rehabilitation using a Maryland bridge. The outcome of the treatment showed improved dental esthetics, harmonious soft-tissue profile, and parallel roots. This case highlights the importance of early intervention for alveolar clefts and the collaborative effort required for comprehensive oral rehabilitation in cleft lip and palate patients.